Adaptive interference mitigation space‐time array reconfiguration by joint selection of antenna and delay tap - Sun, Yandong; Xie, Jian; Gong, Yanyun; Zhang, Zhaolin; Wang, Ling (IET radar, sonar & navigation, 2024)
Space‐time adaptive processing (STAP) array has found extensive use in the global navigation satellite system for interference suppression. Nevertheless, the conventional space‐time array necessitates multiple antennas and time delay taps, resulting in a heavy burden on both hardware and computation resources. Thus, lowering the cost and complexity of STAP becomes a considerable problem demanding prompt solutions. This work designs a space‐time array reconfiguration scheme based on the joint selection strategy of the antenna and delay tap to address this problem. The reconstructed array can induce a high signal to interference plus noise power ratio (SINR) when using fewer antennas and delay taps. The space‐time correlation coefficient (STCC) is first presented to manifest the influence of reconfiguration on output SINR. Then, we formulate the space‐time array reconfiguration mathematical model, aiming to minimise STCC. Two reconfiguration methods are provided to solve the optimal array configuration of antennas and delay taps that can reach the minimum STCC and maximum SINR. The optimal antenna‐delay tap pairs are finally selected to comprise the reconstructed array. Substantial simulation experiments verify that the presented scheme and strategy are effective and reliable in space‐time array reconfiguration. Combining the STAP technique and joint selection of antenna and delay tap, we devise a space‐time array reconfiguration technique applied to GNSS. The reconstructed space‐time array can induce a high SINR when using fewer antennas and delay taps, thus reducing the design cost and achieving superior interference suppression performance.